2003
DOI: 10.1074/jbc.m208766200
|View full text |Cite
|
Sign up to set email alerts
|

RNase L Mediates Transient Control of the Interferon Response through Modulation of the Double-stranded RNA-dependent Protein Kinase PKR

Abstract: (1) and mRNA turnover regulation by the AU-rich elements in the 3Ј-untranslated regions (2). The IFN antiviral response is a highly regulated process involving the transient inhibition of viral and cellular protein synthesis. The translational inhibition is mediated predominately by the activity of PKR, the double-stranded RNAdependent protein kinase. PKR is a serine/threonine protein kinase of 65 and 68 kDa in murine and human cells, respectively, that is induced by IFN treatment of cells and phosphorylates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 41 publications
1
46
0
1
Order By: Relevance
“…Meanwhile, in complementary work, Catherine Bisbal and co-workers were successful in cloning the RNase L inhibitor (RLI), an ATP binding cassette protein also known as ABCE1 [55]. Khalid Khabar showed that RNase L could affect the stability of PKR mRNA and levels of PKR, demonstrating that the two pathways are in a type of balance [56]. Studies by the groups of Robert Suhadolnik [57,58] and Bernard LeBleu [59,60] described up-regulation of the 2-5A system and accumulation of a 37 kDa polypeptide from RNase L in PBMC of patients with chronic fatigue syndrome.…”
Section: Molecular Cloning Of Rnase Lmentioning
confidence: 99%
“…Meanwhile, in complementary work, Catherine Bisbal and co-workers were successful in cloning the RNase L inhibitor (RLI), an ATP binding cassette protein also known as ABCE1 [55]. Khalid Khabar showed that RNase L could affect the stability of PKR mRNA and levels of PKR, demonstrating that the two pathways are in a type of balance [56]. Studies by the groups of Robert Suhadolnik [57,58] and Bernard LeBleu [59,60] described up-regulation of the 2-5A system and accumulation of a 37 kDa polypeptide from RNase L in PBMC of patients with chronic fatigue syndrome.…”
Section: Molecular Cloning Of Rnase Lmentioning
confidence: 99%
“…This pathway is reviewed by Silverman and Bisbal in this same issue. In recent years, it has been accepted that RNase L participates in the degradation of selected cellular mRNAs [63][64][65][66][67]. Specifically, RNase L has been shown to downregulate PKR mRNA [64].…”
Section: The Role Of Ifn-regulated Rnase L and Pkr In The Post-transcmentioning
confidence: 99%
“…In recent years, it has been accepted that RNase L participates in the degradation of selected cellular mRNAs [63][64][65][66][67]. Specifically, RNase L has been shown to downregulate PKR mRNA [64]. During the IFN antiviral response in normal cells, PKR mRNA expression is transient, but in RNase L-null cells, extended kinetics of PKR mRNA expression is observed, due to increased mRNA stability [64].…”
Section: The Role Of Ifn-regulated Rnase L and Pkr In The Post-transcmentioning
confidence: 99%
See 2 more Smart Citations